Observance of preoperative clear fluid fasting in pediatric anesthesia: oral and written information versus text message information. A before‐and‐after study. Issue 5 (25th February 2021) - Thomasseau, Alexandre; Rebollar, Yohann; Dupuis, Maxime; Marschal, Nathalie; Mcheik, Jiad; Debaene, Bertrand; Frasca, Denis; Boisson, Matthieu
Abstract: Introduction: Prolonged fasting before surgery is common in pediatrics. In the literature, it is responsible for hypotension, irritability and postoperative nausea and vomiting. Despite clear instructions given during the preanesthetic consultation, fasting rules are respected in only 30%–40% of cases. We aimed to evaluate the benefit of sending a text message the day before surgery to improve the parents' observance of fasting rules. Methods: We conducted a before‐and‐after study at the University Hospital of Poitiers. From August to October 2018, 172 parents of children under 15 years of age scheduled for all types of surgery were enrolled into two groups according to the period: the control group with parents receiving information on preoperative fasting rules during the preanesthetic consultation several days before surgery, and the text message group, receiving the same information during consultation plus a text message the day before the surgery. Results: There was a difference in observance of clear fluid fasting instructions (between 2 and 3 h before the admission at hospital) in favor of the text message group 33% versus 92% OR 29.2 (10.9–95.2) p  < 0.001, and in average fasting time for clear fluids 8.7 h ± 4.8 h vs. 4.3 h ± 2.4 h ( p  < 0.001). Conclusion: Sending of a reminder text message to the parents the day before the surgery resulted in a significant increase in observance of fasting rules in children undergoing scheduled surgery.